A Business Feasibility Study for Glassware Production at CV Angga Putra Sejahtera - Yulianti, Dini; Agustina, Amelia (Universitas Insan Cendekia Mandiri, 2024)
A business feasibility study is needed when a business owner wants to know whether the business to be run is profitable or vice versa, as in this study where CV. Angga Putra Sejahtera as a company wants to create an MSME company that makes glass products. The method used in this study starts from the market and marketing aspects by using the 4P marketing mix strategy and forecasting with the time-series model method. In the technical and technological aspects with the selection of the type of layout (layout), making the flow of the production process and production capacity, and the thing that becomes the focus of decision making on a project is the financial aspect where the method of calculating investment appraisal The results of this study explain the strategy used by this business is feasible. based on the market mix strategy and the appropriate forecasting results using a linear trend which has the smallest forecasting error value compared to other methods with the results obtained is the Mean Squared Error (MSE) Method of 1073.103. The layout chosen is the process layout because it looks at the process flow map that must be carried out sequentially until production is complete with a daily production capacity of 39 pcs for 6000 yards of yarn. The results of the financial analysis obtained a Net Present Value (NPV) of Rp698.188.945,536, with a Break event Point (BEP) of 4068 units/years, a Payback Period (PP) of 11 months, and an Internal Rate of Return (IRR) of 20,33%.